Women in Science : Plenary Address on 8th Nov. 2009, for Session on Speech, Language & Hearing Sciences and Disorders at the 2nd National Women's Science Congress hosted by AIISH, Mysore - Prathibha Karanth (Journal of All India Institute of Speech and Hearing, 2010)
Speech language pathology has largely been viewed as a 'woman's profession'. Support for this view is found in the fact that women form the majority of field workers in the profession. Yet the prevalence and impact of women, be it in positions of power within the field, or as speech language pathology scientists, has been negligible. The paper explores the possible reasons for the same and how this needs to be and can be changed in the future.